2000
DOI: 10.1007/bf02853163
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of cardiac involvement in myotonic dystrophy (Steinert’s Disease): A 13-year follow-up study

Abstract: Myotonic dystrophy (MD) is associated with a wide spectrum of cardiac abnormalities, but only a few longitudinal studies have investigated the natural course of heart disease in MD. To assess whether neuromuscular involvement significantly predicts cardiac disorders in MD, 83 patients with various grades of disease severity were enrolled in a 13-year follow-up study (mean, 60.6 +/- 37.8 months) that included periodic physical and instrumental cardiac examinations (standard and Holter electrocardiography, echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…Nine (n = 609) studies reported echocardiographic findings on LVEF above or less than 50% [10][11][12][13][14][15][16][17][18]. The patients' gender was not reported in 266 patients.…”
Section: Cardiac Imaging and Lvefmentioning
confidence: 97%
“…Nine (n = 609) studies reported echocardiographic findings on LVEF above or less than 50% [10][11][12][13][14][15][16][17][18]. The patients' gender was not reported in 266 patients.…”
Section: Cardiac Imaging and Lvefmentioning
confidence: 97%
“…Many studies have been performed to find variables that could help predict which patients are at increased risk for an adverse cardiac event (15)(16)(17)(18)(19)(20)(21)(22)(23). These studies, using different approaches, usually showed that advancing age and severity of neurological impairment, and a higher degree of conduction disturbance, assessed either by surface electrocardiogram (ECG) or by electrophysiological study, correlate with a worse outcome.…”
mentioning
confidence: 99%
“…First degree (prolonged) AV conduction block is common in DM1. Higher grade AV conduction block and ventricular tachycardia are associated with "sudden death" in DM1 (10,29).…”
mentioning
confidence: 99%